2008
DOI: 10.1002/chem.200800218
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Reaction of Radicals with Peroxides and Dimethyl Sulfoxide in Aqueous Solution

Abstract: The reactions of methyl and methylperoxyl radicals derived from dimethyl sulfoxide (DMSO) with hydrogen peroxide, peroxymonocarbonate (HCO4 (-)), and persulfate were studied. The major reaction observed for the hydroperoxides was the abstraction of the hydrogen atom by the radicals. The radicals interact with a lone pair of electrons on the peroxide to produce methanol and formaldehyde. Furthermore, the results indicate that in RO2H and RO2R', electron-withdrawing groups cause a considerable increase in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…CH 4 formation from DMSO has been described before [26][27][28] : hydroxyl radicals, produced via radiolysis of water or via Fenton's reaction, have been shown to react with DMSO to produce methyl radicals. This reaction leads to CH 4 , ethane (C 2 H 6 ), methanol and/or formaldehyde, depending on the reaction conditions [26][27][28][29] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CH 4 formation from DMSO has been described before [26][27][28] : hydroxyl radicals, produced via radiolysis of water or via Fenton's reaction, have been shown to react with DMSO to produce methyl radicals. This reaction leads to CH 4 , ethane (C 2 H 6 ), methanol and/or formaldehyde, depending on the reaction conditions [26][27][28][29] .…”
Section: Resultsmentioning
confidence: 99%
“…This reaction leads to CH 4 , ethane (C 2 H 6 ), methanol and/or formaldehyde, depending on the reaction conditions [26][27][28][29] . However, under conditions used in our experiments (iron(II/III), ASC and H 2 O 2 ), when FH is replaced by water-soluble iron salts that are believed to produce hydroxyl radicals (Fenton's reaction), very little CH 4 production was observed (o1%; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[26,42,43] The reaction of DMSO with hydroxyl radicals resulting in the formation of methyl radicals and CH 3 SOOH is well known in radical chemistry. [44] However, recent studies concerning the radical reactions of DMSO have confirmed that the generation of methyl radicals is not selectively restricted to the reaction with hydroxyl radicals, and…”
Section: Epr Spin Trapping Study Of Photoinduced Processes Of Selenadmentioning
confidence: 99%
“…[42] Methyl radicals generated in the presence of molecular oxygen rapidly form methyl peroxy radicals, which react with the spin trapping agent DMPO generating the unstable spin-adduct…”
Section: Epr Spin Trapping Study Of Photoinduced Processes Of Selenadmentioning
confidence: 99%
“…tert-Butanol and dimethyl sulphoxide (DMSO) [36] were introduced into the CL system to further characterize the generation of ·OH. t-Butanol has reaction constant with hydroxyl radicals of 6 × 10 8 mol/L s 1 [37].…”
Section: Thiourea T-butanol and Dmso Experiments For ·Ohmentioning
confidence: 99%